1930
DOI: 10.1109/t-aiee.1930.5055702
|View full text |Cite
|
Sign up to set email alerts
|

Voltage oscillations in armature windings under lightning impulses-I

Abstract: Synopsis.-Experience has shown that rotating machinery theory developed, and oscillographic evidence supporting their connected directly to overhead lines is more vulnerable to surges reliability is given. A generalized theory of neutral protection is than many other types of apparatus. This fact together with a proposed. The importance of wave-front, surge impedance of desire on the part of some to connect important units to the line incoming line, arrester resistance, and other factors is discussed. in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1939
1939
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…As presented in a recently published article [1], research concerning non-uniform potential distributions in electrical machine windings dates back to 1930 [2] and even back to 1902 for transformers [3]. It was observed that non-uniform potential distributions occur during voltage transients at the machine terminals which impose abnormal stress on the insulation.…”
Section: Introductionmentioning
confidence: 99%
“…As presented in a recently published article [1], research concerning non-uniform potential distributions in electrical machine windings dates back to 1930 [2] and even back to 1902 for transformers [3]. It was observed that non-uniform potential distributions occur during voltage transients at the machine terminals which impose abnormal stress on the insulation.…”
Section: Introductionmentioning
confidence: 99%